A Comparative Study of Biomimetic Synthesis of EDOT-Pyrrole and EDOT-Aniline Copolymers by Peroxidase-like Catalysts: Towards Tunable Semiconductive Organic Materials - Martínez-Cartagena, Manuel Eduardo; Bernal-Martínez, Juan; Banda-Villanueva, Arnulfo; Magaña, Ilse; Córdova, Teresa; Ledezma-Pérez, Antonio; Fernández-Tavizón, Salvador; Díaz de León, Ramón (Frontiers in Chemistry, 2022)
Biomimetic synthesis of conducting polymers has two decades since first reported, however, the systematic investigation on how catalyst influence on the properties of the conducting polymers has not been reported yet. In this paper, we report a comparative study between peroxidase-like catalyst, dopants, and their effect on the properties of poly (3,4-ethylene dioxythiophene) (PEDOT), polypyrrole (PPY) and polyaniline (PANI). We also investigate the EDOT-Pyrrole and EDOT-Aniline copolymerization by enzymomimetic synthesis using two catalysts (Ferrocene and Hematin). It was found that chemically, the are no detectable effects, only having small contributions in molar ratios greater than 0.7-0.3. Spectroscopic data provide solid evidence concerning the effect in the variation of the molar fractions, finding that as the molar fraction of EDOT decreases, changes associated with loss of the conjugation of the structure and the oxidation state of the chains were observed. The electrical conductivity was considerably modified depending on the type of catalyst. Hematin produces conductive homopolymers and copolymers when doped with p-toluene sulfonic acid (TSA), while ferrocene low conductive copolymers under the same conditions. The mole fraction affects conductivity significantly, showing that as the EDOT fraction decreases, the conductivity drops drastically for both EDOT-PY and EDOT-ANI copolymers. The type of dopant also notably affects conductivity, the best values were obtained by doping with TSA, while the lowest when doping with polystyrene sulfonate (PSS). After all, we draw a biomimetic route to tailor the fundamental properties of conducting homopolymers and copolymers for their design and scale up production, which have been recently found a broad range of applications.